ANALISA HIDROLIS JARINGAN PIPA DISTRIBUSI UTAMA DAN DISTRIBUSI BAGI PADA SISTEM PENYEDIAAN AIR MINUM (SPAM) IKK WASILE TIMUR - Robbi Harisman; Zulkarnain K Misbah; Edward Risky Ahadian (Fakultas Teknik Universitas Khairun, 2018)
The existing water resources need to be sustainably managed. Sustainable water resource management system is a managed and managed water resources management system that fully contributes to current and future societal and economic goals while maintaining its ecological sustainability. This research was conducted by direct observation in the field. Then the data obtained from the field in though by using a computer program. This research activity was conducted in East Wasile Sub-district of East Halmahera Regency of North Maluku Province. The results of this study indicate that the diameter of the pipe used is 300 mm diameter, 250 mm, 200 mm, 150 mm, 100 mm, and 63 mm. From the variation of the pipe obtained Maximum pressure 49.37 m or equal to 4.937 bar while minimum pressure of 26.39 m or equal to 2,639 bar. The pressure of the analysis result meets the criteria of distribution network planning that is maximum 9.0 - 12.4 bar and minimum 0.5 - 1.0 bar. Maximum flow velocity of 0.60 m/s and a minimum speed of 0.30 m/s flow velocity on the analysis results meets the planning criteria which according to the provisions of a maximum of 2.5 m/s and a minimum of 0.25 m/s.